The Impact of Blue Light Exposure on Cortisol Secretion and Psychophysiological Readiness in Sport - Popczyk, Michał; Świątecka, Martyna; Przybyłowska, Agnieszka; Bryksy, Sylwia; Buczkowska, Ewa; Kaźmierczyk, Jakub; Tymchenko, Hanna; Piechowicz, Agnieszka; Popczyk, Natalia; Marciszewska, Aleksandra (Quality in Sport, 2026)
Introduction: Cortisol is a crucial stress hormone regulated by the hypothalamic-pituitary-adrenal (HPA) axis. Its secretion is intricately linked to the central biological clock and the suprachiasmatic nucleus in hypothalamus (Figueiro & Rea, 2010). Although the interaction between light exposure and cortisol secretion is indicated in numerous studies, the effect of specific light on the cortisol secretion during stress response is not yet fully understood (Petrowski et.al, 2021a). Blue light is characterized by a short wavelength and high-energy and is present of natural sun light, and artificial light. It is a key for regulating circadian rhythms. Purpose of Work: This review is a comprehensive summary of mechanisms through which different light spectra affect cortisol secretion in several contexts, such as stress reaction, sleep-restriction, and seasonal changes, taking into consideration health implications. Materials and methods: A comprehensive literature search was conducted in the Google Scholar and PubMed databases from 1998 onward. The review included controlled laboratory, longitudinal, clinical and field studies that investigated the impact of various types of light on cortisol secretion. Summary: The evidence indicates a stimulatory effect of exposure to blue and bright light on cortisol secretion primarily targeting the cortisol rising phase (post-awakening) or night time, and strengthening cortisol stress reaction. In context of sleep limitation, daytime light exposure mitigates morning decline in cortisol. However, prolonged exposure to extremely bright white light suppresses cortisol secretion, but only when its level is already elevated. Furthermore, the review identifies light manipulation as a non-invasive tool for optimizing athletic performance. Blue light exposure stimulates the anticipatory cortisol response required for activation and cognitive readiness, whereas red light facilitates recovery and reduces pre-competitive anxiety.